Recovery and Purification of Used Lubricating Oil Through Solvent Extraction: Empirical Validation and Process Optimization - Maha A Dawood (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Mismanagement of used lubricating oil represents a significant environmental and economic challenge due to the loss of valuable hydrocarbon resources and contamination risks to land and water systems. Specific Background: Solvent extraction technology has emerged as a promising recycling approach capable of removing contaminants and restoring physicochemical characteristics of degraded lubricating oil while supporting resource conservation strategies. Knowledge Gap: However, limited empirical validation combining solvent selection with operational parameter optimization and predictive modeling for oil recovery rate remains insufficiently addressed. Aims: This study evaluates solvent extraction performance using several solvent systems and optimizes key process parameters, including solvent-to-oil ratio, temperature, and pressure, while developing regression-based predictive models for oil recovery rate and impurity removal. Results: Findings indicate that a propane-based solvent mixture increased recovery rate and reduced secondary waste generation, with optimal operating conditions identified at a solvent-to-oil ratio of 4:1, temperature range of 180–220 °C, and pressure of 4–10 mbar; regression modeling demonstrated strong agreement between experimental and calculated values with accuracy of 94.98 and variance of 0.016. Novelty: The integration of comparative solvent evaluation with empirical least-squares regression modeling provides validated relationships linking solvent composition and operational variables to recovery performance. Implications: These outcomes support solvent extraction as a sustainable pathway for recycling used lubricating oil, enabling improved resource utilization while reducing environmental burdens associated with conventional disposal practices. Highlights: • Parameter Window 200 °C and 4–8 Mbar Produced Highest Distilled Volume• Regression Prediction Reached 94.98 Accuracy With 0.016 Variance• 4:1 Ratio Minimized Reagent Consumption While Maintaining Yield Keywords: Used Lubricating Oil Recovery, Solvent Extraction Process, Propane Solvent Mixture, Process Parameter Optimization, Oil Recovery Rate Modeling